2022
DOI: 10.1038/s41433-021-01925-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriostatic preserved saline for pain-free periocular injections: review

Abstract: We review evidence regarding the use of 0.9% benzyl alcohol in 0.9% sodium chloride solution for periocular injections (‘preserved saline’) including botulinum toxin A injections and local anaesthesia. A literature search was undertaken using search terms ‘bacteriostatic saline’, ‘benzyl-alcohol saline’, ‘benzyl alcohol sodium chloride’ and ‘preserved saline’. Bibliographies identified further sources. There have been 62 studies published on the subject of preserved-saline since 1928. Significantly lower injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A hydropathic compress of alcohol has an anaesthetic effect on local tissues and nerves, thus reducing the pain suffered by patients. Furthermore, alcohol is a bacteriostatic drug, which can prevent local tissue infection and reduce local reaction [18].…”
Section: Discussionmentioning
confidence: 99%
“…A hydropathic compress of alcohol has an anaesthetic effect on local tissues and nerves, thus reducing the pain suffered by patients. Furthermore, alcohol is a bacteriostatic drug, which can prevent local tissue infection and reduce local reaction [18].…”
Section: Discussionmentioning
confidence: 99%
“…Dilution with bacteriostatic saline consisting of 0.9% benzyl alcohol in 0.9% sodium chloride is shown to reduce patientperceived pain related to periorbital injections of local anesthetic and improve comfort better than buffering with 8.4% sodium bicarbonate. [5][6][7][8][9] Bacteriostatic saline has no impact on the potency of epinephrine in terms of duration of action or vasoconstriction and can be added to any local anesthetic without the formation of precipitate. There are a number of additional advantages to this approach, including: 1.…”
Section: Anestheticsmentioning
confidence: 99%
“…The authors have used a protocol for over 20 years in which standard 2% lidocaine with 1:100,000 epinephrine is diluted 1:5 with plain or bacteriostatic saline for an initial injection that attempts to fully anesthetize all surgical sites. Dilution with bacteriostatic saline consisting of 0.9% benzyl alcohol in 0.9% sodium chloride is shown to reduce patient-perceived pain related to periorbital injections of local anesthetic and improve comfort better than buffering with 8.4% sodium bicarbonate 5–9 . Bacteriostatic saline has no impact on the potency of epinephrine in terms of duration of action or vasoconstriction and can be added to any local anesthetic without the formation of precipitate.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials for BoNTA product approvals, the products are reconstituted in normal (unpreserved) saline (0.9% NaCl) as reflected in the product labeling [ 1 , 3 ]. However, in clinical practice, it is common for injectors to reconstitute botulinum toxins in preserved saline (i.e., bacteriostatic saline: 0.9% NaCl preserved with benzyl alcohol) [ 4 ], as it has been found that this results in less procedural pain than when BoNTA is reconstituted in unpreserved saline [ 5 , 6 , 7 , 8 , 9 ]. The product’s stability and sterility after reconstitution are influenced by the excipients formulated with the active pharmaceutical ingredient, in addition to the diluent.…”
Section: Introductionmentioning
confidence: 99%